Study of effectiveness of controlled traffic farming system and wide span self-propelled gantry-type machine - Bulgakov, Volodymyr; Булгаков, Володимир Михайлович; Булгаков, Владимир Михайлович; Adamčuk, V.; Nozdrovický, L.; Kuvachov, Volodymyr; Кувачов, Володимир Петрович; Кувачев, Владимир Петрович (My University, 2018)
Trends in the global agricultural sector tend to efficient use of resources and improving the quality in agriculture. A significant effect in this regard can be achieved when using controlled traffic farming and wide span self-propelled gantry-type machine. The aim of this study is theoretical justification of the cost-effectiveness of introduction of the controlled traffic farming system and using of wide span self-propelled gantry-type machine, by selecting some optimal parameters of land use. Provided studies have shown that the most significant economic effect of introduction of the controlled traffic farming system is evident on the fields with high anthropogenic degradation of soils, where the results of crop yields increasing due to natural processes of soil decompression will be essential. The economic effect obtained by the implementation of the controlled traffic farming system by saving energy costs and seed. and due to increased crop yields is a minimum at the level of 150 € per ha.
Keywords: precision agriculture; field machine passes; time utilization; reduction of the soil compaction; economic efficiency